2015
DOI: 10.1007/s12010-015-1785-x
|View full text |Cite
|
Sign up to set email alerts
|

New Insights on Coffea miRNAs: Features and Evolutionary Conservation

Abstract: Small RNAs influence the gene expression at the post-transcriptional level by guiding messenger RNA (mRNA) cleavage, translational repression, and chromatin modifications. In addition to model plants, the microRNAs (miRNAs) have been identified in different crop species. In this work, we developed a specific pipeline to search for coffee miRNA homologs on expressed sequence tags (ESTs) and genome survey sequences (GSS) databases. As a result, 36 microRNAs were identified and a total of 616 and 362 potential ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 61 publications
(57 reference statements)
1
17
0
Order By: Relevance
“…Furthermore, most of the observed miR167 targets in plants were related to the hormonal pathways regulation, as in A . thaliana , rice and coffee 154 , 186 , 187 . Considering that miR167 plays these important roles, such as responses to heat shock, nitrogen stress and hormonal pathway regulation, its higher expression in S .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, most of the observed miR167 targets in plants were related to the hormonal pathways regulation, as in A . thaliana , rice and coffee 154 , 186 , 187 . Considering that miR167 plays these important roles, such as responses to heat shock, nitrogen stress and hormonal pathway regulation, its higher expression in S .…”
Section: Discussionmentioning
confidence: 99%
“…A most recent study using computational approaches identified 16 possible miRNAs in C. arabica and 20 in C. canephora all of which belong to 26 different families and 7 new miRNAs (car-MIR7122, car-MIR835, cca-MIR368, cca-MIR3169, cca-MIR5293, cca-MIR6459, and cca-MIR845). These identified coffea miRNA families regulated potential target genes involved in various biological processes and they strongly influence growth patterns, such as plant development, hormonal responses, mature mRNA formation, stress responses, and cellular signaling pathways (Chaves et al, 2015). …”
Section: Functional Roles Of Mirnasmentioning
confidence: 99%
“…This duplex then undergoes methylation at 3′ terminus by HUA ENHANCER1 (HEN1) to protect them against degradation by small RNA degrading exonuclease, SDN. The pre-miRNAs or the mature miRNAs are then exported from nucleus to the cytoplasm by the plant exportin protein HASTY (Chaves et al, 2015 ). One strand of the duplex in cytoplasm gets unwound into a single stranded mature-miRNA which then gets incorporated into an ARGONAUTE protein, and directs RNA induced silencing complex (RISC) binding to cognate target transcripts through sequence complementarities (Voinnet, 2009 ; Khraiwesh et al, 2010 , 2012 ).…”
Section: Plant Mirnas: Their Biogenesis Targets and Mode Of Actionmentioning
confidence: 99%